# How to solve simultaneous equation

*1,795*pages on

this wiki

## Ad blocker interference detected!

### Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.

simultaneous equation can be solve for by hand or using computers.

*the examples below will use the following equations*

*equation 1:*(x+3)^2 + (y-1)^2 = 25*equation 2:*(x-2)^2 + (y+4)^2 = 9*solve for:*x, y

## Substitution method Edit

- Evaluate one of the variables over other variables
- Substitute the variable in the next equation by the evaluated variable

## Using Maple 10Edit

Maple 10 is an advanced mathematical computational program used for solving and performing math based simulations Maple can easily be used to solve simultaneous equations.

### Method 1Edit

Substitution by hand:

restart; eq1 := (x+3)^2 + (y-1)^2 = 25; solve(eq1);

We get that x = **-3+sqrt(24-y^2+2*y)**, so we write the second equation substituting x with the expression by hand, and repeat the solve function:

eq2 := ((-3+sqrt(24-y^2+2*y))-2)^2 + (y+4)^2 = 9 solve(eq2);

We get the answer:

x_{1} = -23/10, y_{1}=-sqrt(161)/10

x_{2} = -23/10, y_{1}=+sqrt(161)/10

### Method 2Edit

Alternatively, one may use the solve function to solve both equations simultaneously, using a single command:

solve({2*x - 6*y + 3 = 0, 3*y^2 - 6*x + 6 = 0}, [x, y]);